Symposium: Emerging Perspectives on the Internationalization of Curriculum Studies - Kumar, Ashwani; Brigham, Susan M.; Downey, Adrian M.; Lemieux, Amélie; Kharbach, Mohamed; Petersen, Bonnie; Wiebe, Sean (Journal of the Canadian Association for Curriculum Studies, 2020)
This symposium is concerned with understanding the forces that shape and influence curriculum in international contexts. The study of curriculum in international contexts reveals the insidious impacts of colonial, ideological and neoliberal influences on contemporary curriculum development in a variety of geo-cultural, political and economic contexts (Kumar, 2019). Four theoretical responses—Indigenous, critical, autobiographical and meditative—that provide thoughtful perspectives to challenge these negative influences will be explored in the symposium. The impact of intellectual movements such as Marxism and postmodernism on curriculum theory in varied political and economic settings will also be underscored. The symposium invites and initiates a complicated conversation around the internationalization of curriculum studies by inviting panelists from posthuman, Indigenous, black feminist, critical discursive and foundational perspectives to respond to the aforementioned colonial, ideological and neoliberal influences on curriculum development.